2016
DOI: 10.1093/ejcts/ezw296
|View full text |Cite
|
Sign up to set email alerts
|

Lamininα2-secreting fibroblasts enhance the therapeutic effect of skeletal myoblast sheets

Abstract: Laminin secreted by implanted fibroblasts inhibited the detachment of implanted myoblasts from grafted myocardia, resulting in more permanent therapeutic effects upon myoblast sheet transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…After confirming the adherence of the first sheet, subsequent sheets were applied using the same technique, as described previously. [21][22][23]…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…After confirming the adherence of the first sheet, subsequent sheets were applied using the same technique, as described previously. [21][22][23]…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The cardiac function of the treated rats was monitored by echocardiography both before surgery and at 2, 4, 6, and 8 weeks after gel implantation or at 2 and 4 weeks after cell sheet implantation using a system equipped with a 12-MHz transducer and a SONOS 5500 device (Agilent Technologies, Santa Clara, Calif) under isoflurane inhalation (2%), as described previously. 19,22,23…”
Section: Measurement Of Cardiac Function By Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the ECM is the “theatre” where most cues or signals from diverse sources are integrated into a “specific” message that is relayed to cells. The ECM is synthesised mostly by fibroblasts with the contribution of other cells such as mesenchymal stem cells, macrophages and endothelial cells [ 31 , 32 , 33 , 34 , 35 , 36 ]. Fibroblasts are the main cellular components of tumor stroma [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in future research, we should focus more on the combination of multiple cell sources in the fabrication of cell sheet. For example, some papers showed that the combination of fibroblasts expressing laminin G-module 4-5 of α2 and SMs in multilayered sheet markedly inhibited the detachment of implanted myoblasts from sheet, resulting in more permanent and stable efficacy on single myoblast sheet because fibroblasts could abundantly embed in the myoblast layer to fasten and support the structure via extracellular matrix production [58]. Another report showed that the local release of VEGF enhanced the transplantation efficiency of layered cardiomyocyte sheet, which could be related to vascularization [70].…”
Section: Mesenchymal Stem Cell-derived Cell Sheetmentioning
confidence: 99%